2014
DOI: 10.1167/iovs.13-13496
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Changes in High Myopia Observed by Swept-Source Optical Coherence Tomography

Abstract: Highly myopic eyes may have larger PPVPs than normal eyes. Partial PVDs around the macula and complete PVDs occur at younger ages. The vitreous cortex more frequently remains on the macula after development of complete PVDs in highly myopic eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 25 publications
4
68
0
Order By: Relevance
“…Finally, myopia was also a common denominator in five of the six patients presented, and vitreoretinal interface alterations influenced by myopia are well described. [6][7][8] In summary, we report the 'shadow sign' with CHRPE lesions in young, myopic, pigmented patients, which may simulate the clinical appearance of subretinal fluid and/ or lesion thickness. Clinicians must be aware that this sign may cause a benign process to appear malignant on ophthalmoscopy, and we recommend the use of ancillary testing as appropriate to rule out the possibility of choroidal melanoma.…”
Section: Discussionmentioning
confidence: 79%
“…Finally, myopia was also a common denominator in five of the six patients presented, and vitreoretinal interface alterations influenced by myopia are well described. [6][7][8] In summary, we report the 'shadow sign' with CHRPE lesions in young, myopic, pigmented patients, which may simulate the clinical appearance of subretinal fluid and/ or lesion thickness. Clinicians must be aware that this sign may cause a benign process to appear malignant on ophthalmoscopy, and we recommend the use of ancillary testing as appropriate to rule out the possibility of choroidal melanoma.…”
Section: Discussionmentioning
confidence: 79%
“…It was observed that vitreous cortex frequently remained on the retina in highly myopic eyes despite a Weiss ring. Using SS OCT in a case-control study, Itakura et al 21 found the presence of residual vitreous cortex in 40.5% of highly myopic eyes, compared with only 8.7% of controls. Vitreoschisis may be related to the underlying multi-lamellar structure of the posterior wall of PPVP, which can be split into separate layers during anomalous PVD.…”
Section: Assessment Of Vitreous By Oct In Myopiamentioning
confidence: 99%
“…Since then, several publications have used SS-OCT to examine the vitreous in health and disease. [9][10][11][12][13][14] However, although the premacular bursa and its relationship to Cloquet's canal have been the subject of relatively intense study, 2,9,10 PVF and vitreous cisterns have not been described using this noninvasive imaging method. The aim of this study was to characterize PVF and vitreous cisternal spaces in vivo with SS-OCT imaging, which may be relevant to vitreoretinal interface diseases and vitreous pharmacodynamics.…”
mentioning
confidence: 99%